Women at war in the borderlands of the early American Northeast - Martino, Gina M. (David J. Weber series in the new borderlands history., 2018)
"Across the borderlands of the early American Northeast, New England, New France, and native nations deployed women with surprising frequency to the front lines of wars that determined control of North America. Far from serving as passive helpmates in a private, domestic sphere, women assumed wartime roles as essential public actors, wielding muskets, hatchets, and makeshift weapons while fighting for their families, communities, and nations. Revealing the fundamental importance of martial womanhood in this era, Gina M. Martino places borderlands women in a broad context of empire, cultural exchange, violence, and nation building, demonstrating how women's war making was embedded in national and imperial strategies of expansion and resistance. As Martino shows, women's participation in warfare was not considered transgressive; rather it was integral to traditional gender ideologies of the period, supporting rather than subverting established systems of gender difference"--